Конвективный теплоперенос в одной пространственной задаче теплопроводности - Шевченко, А.И.; Миненко, А.С. (Видавничий дім "Академперіодика" НАН України, 2007)
A three-dimensional non-stationary problem of thermal conductivity considering the convective motion in the fluid phase is investigated by the series expansion in the small Reynolds number. The formula of the dependence of a free boundary equation on the Reynolds number is obtained